Effect Of Apple Juice On Whitening Teeth After Immersion In Coffee Solution In Vitro - Puspasari, Nuzulya; Effendi, Chair; Nugraeni, Yuli (Universitas Muhammadiyah Yogyakarta, 2012)
The Background of this research because one of the extrinsic cause teeth discoloration is excessive coffee consumption. To cope teeth discoloration whitening teeth done either with chemicals or natural ingredients. Apples (Malus sylvestris Mill) is one of the fruits that contain malic acid, substance that can whitening teeth. The General Objective is to determine the effect of giving apple juice (Malus sylvestris Mill) on a teeth that has been soaked in coffee solution on teeth whitening in vitro. Materials and Methods research is experimental laboratory use elements of the permanent maxillary premolar tooth from extraction indications orthodontic treatment, free of caries and hypoplasia as a sample of 12 pieces, divided into 2 groups. The first group as a control group with 100 ml distilled water immersion. The second group as the treatment group using apple juice immersion with 75% concentration. Samples of tooth element has immersed first in coffee solution during 2 weeks until discoloration then immersed according to the group for 2 weeks (3x@5minutes a day), then measured the color changes of tooth. The Result with Paired T-test showed significant effect on the group before treatment and after treatment (p 0.05). Independen T-test result showed significant difference between the control group immersed in 100 ml distilled water and treatment group, immersed in apple juice 75% concentration. Conclusion of the results showed that apple juice has the ability to whiten the tooth enamel surface that changes color because of immersion in coffee solution so it can return to the original color before discoloration.